STUDI LITERATUR SEPUTAR TUJUAN PENDIDIKAN ISLAM MENURUT AL QUR’AN DAN HADIS - Sangkot Abdullah Effendi Harahap; Ahmad Wildan; Bobby Irawan; Muhammad Rizky Ihsan; Muhammad Saputra; Rio Agus Susanto (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Islam places great importance on education, highlighting that the religion has a strong basis and clear goals concerning the necessity of acquiring knowledge. Consequently, this document aims to illustrate the Islamic goals in guiding its adherents to emphasize the importance of education. The conversation takes place by exploring Quranic verses related to educational objectives, which are then analyzed by considering different interpretations (tafsir) without restricting it to just one source. Furthermore, this research gathers numerous hadiths associated with educational goals to achieve a thorough understanding of the idea of education in Islam. The analysis incorporates the perspectives of Muslim scholars as comparative material to enhance the academic discussion surrounding the objectives of Islamic education. Additionally, the ideas of contemporary Western educators are employed as a benchmark in analyzing educational goals through the lens of the Quran and Hadith